Effects of music training in executive function performance in children: A systematic review - Rodriguez-Gomez, Diego Alejandro; Talero-Gutiérrez, Claudia (Frontiers in Psychology, 2022)
Music training has traditionally been a fundamental component of children's education across several cultures. Moreover, music training has been hypothesized to enhance the development of executive functions and improve executive performance in children. In this systematic review, we analyze the available evidence of the effects of music training on executive function performance, evaluated using validated neuropsychologic batteries and classic tasks. To achieve this objective, we performed a systematic search in three databases (PubMed, Ovid MEDLINE, and Scopus) and selected case-control or intervention studies conducted on children with neurotypical development. We analyzed 29 studies that met the inclusion criteria and observed significant heterogeneity among the music interventions and methods for assessing executive functions. The review of the available literature suggests a beneficial effect of music training in core executive function performance, primarily in inhibitory control, and to a lesser extent, in working memory and cognitive flexibility.